2022
DOI: 10.3390/ijms23073866
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylserine Induces MUC5AC Production via the Feedforward Regulation of the TACE-EGFR-ERK Pathway in Airway Epithelial Cells in a Receptor-Independent Manner

Abstract: Lysophosphatidylserine (LysoPS) is an amphipathic lysophospholipid that mediates a broad spectrum of inflammatory responses through a poorly characterized mechanism. Because LysoPS levels can rise in a variety of pathological conditions, we sought to investigate LysoPS’s potential role in airway epithelial cells that actively participate in lung homeostasis. Here, we report a previously unappreciated function of LysoPS in production of a mucin component, MUC5AC, in the airway epithelial cells. LysoPS stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…TG is hydrolyzed to provide FA for many cellular processes, such as lipid synthesis and energy production [ 27 ]. Additionally, lysophosphatidylserine (LPS) is an amphipathic lysophospholipid, which mediates the inflammatory response [ 28 ]. By studying the role of LPS in airway epithelial cells that were involved in lung homeostasis, it was found that LPS has a potential receptor-independent role during inflammation [ 28 ], which provides new insights for subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TG is hydrolyzed to provide FA for many cellular processes, such as lipid synthesis and energy production [ 27 ]. Additionally, lysophosphatidylserine (LPS) is an amphipathic lysophospholipid, which mediates the inflammatory response [ 28 ]. By studying the role of LPS in airway epithelial cells that were involved in lung homeostasis, it was found that LPS has a potential receptor-independent role during inflammation [ 28 ], which provides new insights for subsequent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, lysophosphatidylserine (LPS) is an amphipathic lysophospholipid, which mediates the inflammatory response [ 28 ]. By studying the role of LPS in airway epithelial cells that were involved in lung homeostasis, it was found that LPS has a potential receptor-independent role during inflammation [ 28 ], which provides new insights for subsequent studies. At 96 hpi, LPS was upregulated 1.33 times, including 12 upregulated LPS lipid species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation